Stability of Nonuniform Large Geotextile-Reinforced Cofferdam under Seepage and Excavation Effects - Lu, Xiaochun; Luo, Yue; Ming, Huajun; Zhou, Mi; Zhang, Xihong; Liu, Dingwei (ASCE, 2022)
This paper investigates the failure mechanism of nonuniform large geotextile-reinforced cofferdam under seepage and excavation effects on soft sediments. A numerical model is established and validated with available testing results. Then, parametric studies are carried out to investigate the potential influence factors. This study found that the difference between the upstream and downstream water levels and the excavation depth both have significant influences on the stability of cofferdams, where excavation is the key influence factor affecting the stability of the cofferdam. Numerical results revealed that the safety factor could reduce by about 20% with excavation of about 1.5 m. An empirical equation is proposed for quantitative prediction of the stability of geotextile-reinforced cofferdams. A thorough understanding about the failure mechanisms of cofferdams as well as an empirical formula for predicting the stability is concluded in this study, which could provide engineering guide for flexible foundations reinforced by geotextiles.